The Effect Of Change On Some Of The Organisational And Job Factors: A Case Of Introduction Of Cellular Manufacturing - Periaswam, Keamalatha (1998)
This research was conducted to examme the effects of change on some of the organisational and job factors. The factors measured are supervision, communication, job commitment, skill variety and working condition. Factors like age, race, working experience and salary were also included to examine the moderating effect on the above relationship